Overview of the Algerian Insurance Sector in the Era of the Covid-19 Pandemic - Salah Eddine NEBBACHE (المجلة الدولية للأداء الاقتصادي, 2023)
The insurance sector in developed countries occupies a vital place in their economies and contributes to the country's development. This market, like so many others, is doomed to failure, at best, to stagnation. It must therefore be resilient to the economic situation and boost itself to growth. This paper aims to investigate the impact of the double crisis associated with the exceptional economic situation as well as the pandemic on the Algerian insurance sector. The findings reveal that the sector's employment is shrinking, along with a decline in insurance company recruitments. Furthermore, the overall market output is down, notably in the automotive insurance and assistance branches.